The Vermes Quest: The Significance of Geza Vermes for Jesus Research - Møller, Hilde Brekke (Bloomsbury Publishing PLC, 2017)
Cover -- Contents -- Acknowledgements -- List of Abbreviations -- Part I Introduction -- Chapter 1 The Significance of Geza Vermes for Jesus Research -- The Purpose of the Study -- The Problem -- Main Questions, Material, and Method -- Historiographical Considerations and Terminology -- Previous Assessments of Vermes's Jesus Research -- Outline -- Chapter 2 Vermes and Jesus Research -- Biographical Notes on Vermes -- Vermes and Jesus Research -- Vermes's Works on Jesus -- Early Essays -- First Trilogy: The Jewish Jesus -- Second Trilogy: Nativity, Passion, Resurrection -- Follow-ups -- Anthologies -- Vermes's Works as Material for This Study -- Chapter 3 The History of Jesus Research: Mapping the Quest(s) -- The Three-Quest Scheme -- Limitations of the Three-Quest Scheme -- Alternative Mappings of Jesus Research -- The Third Quest -- Part II The Significance of Vermes's Jewish Jesus for Jesus Research -- Chapter 4 Vermes's Jewish Jesus (1973) -- Method and the Jewish Jesus in Jesus the Jew -- A Historian's Reading of the Gospels - Jesus the Jew as Jesus Research? -- Authenticity of Gospel Narratives in Jesus the Jew -- The Historical Jesus of Jesus the Jew -- Vermes's Judaism in Jesus the Jew -- Charismatic Judaism -- Galilee and Galilean Judaism -- Conclusion -- Chapter 5 The Significance of Jesus the Jew: the 1970s and 1980s -- Reviews of Jesus the Jew from the 1970s -- Book Reviews as Sources -- A Varied First Reception -- Jesus the Jew in Histories of the Third Quest from the 1980s -- Conclusion -- Chapter 6 The Jewishness of Jesus before Vermes -- Anti-Semitic Tendencies in Jesus Research -- De-Judaizing Methodology: The Dissimilar Jesus -- Jewish Scholars and the Jewish Jesus -- Christian Scholars and the Jewish Jesus -- German Mission to the Jews and Institutum Judaicum -- Franz Delitzsch and One Day in Capernaum.